Pendangan Ulama Kabupaten Grobogan Terhadap Pelaksanaan Murur Dan Tanazul Pada Musim Haji 2024 - Marjanah, Luk Luul; Sattar, Abdul; Darissurayya, Vina; Hasanah, Hasyim; Muhajarah, Kurnia; Razaq, Abdul (Jayapangus Press, 2025)
This study aims to analyze the views of Grobogan Regency scholars in addressing the murur and tanazul schemes in the 2024 Hajj season. The addition of a quota of 20,000 is an exciting space for Muslims in Indonesia. Complex problems that often occurred in the previous Hajj season related to the accumulation of pilgrims in certain areas such as Muzdalifah and Mina, the increase in the quota given but the lack of space provided made its own concerns for the Indonesian government, especially on the health of the congregation. The research method uses a qualitative method with a descriptive approach. The data collection technique uses interviews that have primary sources from the clerics of MUI, NU, and PDM Grobogan Regency. The informants in this study were selected using purposive sampling technique, namely selecting informants who have knowledge and experience related to the murur and tanazul schemes in the 2024 Hajj season. The results showed that the scholars of Grobogan Regency agreed with the existence of the murur and tanazul schemes in the 2024 Hajj season, with the criteria for the murur scheme being elderly, high-risk, and companion pilgrims, while the tanazul scheme is intended for pilgrims who have strong physical health, because it requires extra energy to walk back to the lodgings because there is no transportation intended for pilgrims who want to do tanazul, only Raudhah and Syiyah lodgings kare.